Sequential injection kinetic flow assay for monitoring glycerol in a sugar fermentation process by saccharomyces cerevisiae - Hueso Domínguez, Karina B. (2010)
A sequential injection system to monitor glycerol in a Saccharomyces cerevisiae fermentation process was developed. The method relies on the rate of formation of nicotinamide adenine dinucleotide in its reduced form (NADH, measured spectrophotometrically at 340 nm) from the reaction of glycerol with NAD+ cofactor, catalysed by the enzyme glycerol dehydrogenase present in solution. This procedure enables the determination of glycerol between 0.046 and 0.46 g/l, (corresponding to yeast fermentation samples with concentrations up to 50 g/l) with good repeatability (relative standard deviation for n = 10 lower than 2.2% for three different samples) at a sampling frequency of 25/h. The detection and quantification limits using a miniaturised spectrophotometer were 0.13 and 0.44 mM, respectively. Reagent consumption was of 0.45 μmol NAD+ and 1.8 μg enzyme per assay, and the waste production was 2.8 ml per determination. Results obtained for samples were in agreement with those obtained with a high-performance liquid chromatography method.